Nudging to improve hand hygiene. Issue 4 (April 2018) - Caris, M.G.; Labuschagne, H.A.; Dekker, M.; Kramer, M.H.H.; van Agtmael, M.A.; Vandenbroucke-Grauls, C.M.J.E.
Summary: Background: Hand hygiene is paramount to prevent healthcare-associated infections, but improving compliance is challenging. When healthcare workers seldom encounter healthcare-associated infections, they will consider the odds of causing infections through poor hand hygiene negligible. Cognitive biases such as these may induce non-compliance. Nudging, 'a friendly push to encourage desired behaviour', could provide an easily implemented, inexpensive measure to address cognitive biases and thus support hand hygiene interventions. Aim: To investigate whether behavioural nudges, displayed as posters, can increase the use of alcohol-based hand rub. Methods: We developed nudges based on a systematic review of previously described cognitive biases, and tested these through a cross-sectional survey among the target audience. We then conducted a controlled before–after trial on two hospital wards, to assess the effect of these nudges on the use of alcohol-based hand rub, measured with electronic dispensers. Findings: Poisson regression analyses adjusted for workload showed that nudges displayed next to dispensers increased their overall use on one ward [poster 1: relative risk: 1.6 (95% confidence interval: 1.2–2.2); poster 2: 1.7 (1.2–2.5)] and during doctor's rounds on both wards [poster 1: ward A: 1.7 (1.1–2.6); ward B: 2.2 (1.3–3.8)]. Use of dispensers without adjacent nudges did not increase. Conclusion: Nudges based on cognitive biases that play a role in hand hygiene, and displayed as posters, could provide an easy, inexpensive measure to increase use of alcohol-based hand rub. When applying nudges to change behaviour, it is important to identify the right nudge for the right audience.